Analisis Rasio Profitabilitas untuk Menilai Kinerja Keuangan PT Astra Agro Lestari TBK Tahun 2019 – 2023 - Ardi Ardi, (Jurnal Publikasi Ilmu Manajemen, 2024)
Ardi, 2024. “ Analysis Profitability Ratio Analysis to Assess the Financial Performance of Pt Astra Agro Lestari Tbk Year 2019 - 2023 “. Thesis Program Management Study Program, College of Management Sciences, Indonesian Institute of Education (STIM-LPI) Makassar which was guided by Mrs. Fausiah, S.E., M.Si. and Mrs. Andi Novita Paramitha, S.H., M.Kn. Research This study aims to determine the financial performance of PT Astra Agro Lestari Tbk if in terms of profitability ratio analysis during 2019 - 2023. Object This research object is a company that focuses on the field of oil palm plantations. This research data, researchers took secondary data with the type of research descriptive quantitative research. Techniques in collecting data obtained from studies documentation of financial statements consisting of balance sheets and profit and loss by using profitability ratio analysis tools in the form of Gross Profit Margin. using profitability ratio analysis tools in the form of Gross Profit Margin (GPM), Net Profit (Net Profit), and Profitability Ratio (Profitability Ratio). (GPM), Net Profit (NPM), Return on Investment (ROI), and Return on Equity (ROE). The results of this study indicate that the financial performance of AAL is not good. This is obtained from the average GPM value of 0.16%, the average NPM value of 0.06%. average NPM value of 0.06%, average ROI value of 0.31, and average ROE value of 0.29%. average ROE of 0.29% with industry standards for each ratio based on cashmere (2019). based on Cashmere (2019) which of course when compared is below the industry standard. industry standards. The decrease in profitability results obtained by the company influenced by the percentage of current assets generated less than activ Translated with DeepL.com (free version)